New approach for using inedible dates in broiler chicken ’s’ diet - BOUAZID, A A; TOPOROVA, L V; TOPOROVA, I V (The Indian Journal of Animal Sciences, 2019)
The aim of this study was to focus on poultry meat quality by studying the effect of using an energy-protein compound (EPC) based on inedible dates, mixed with synthetic amino acids (0.5% lysine and 1% methionine), and a complex of enzymes (α-amylase, β-glucanase) in broiler chicken's diets, which is a part of a larger project to determine whether this compound can be incorporated into Algerian meat production systems without having a negative effect on the overall product quality. Two groups of 50 heads broiler chickens each were used to evaluate nonconventional feed based on inedible dates (EPC) during 42 days. At the end of the experiment, EPC substitute 20% of maize without adversely affecting the rates of growth and mortality. After slaughter, the weight of the femoral muscles of the experimental birds was less than the control birds. But, the weight of the pectoral muscles was significantly higher in the experimental birds' carcasses compared to control group. Analysis of dry matter, protein, fat, and the levels of amino acids showed a significant difference. Control birds had a higher weight of skin and abdominal fat compared to experimental birds. Using energy-protein compound (EPC) based on inedible dates as an alternative for corn in broiler chicken's diets showed positive effect on meat quality, ameliorating weight and amino acids content in broiler's muscles. Thus, EPC can be used as compound to substitute 20% maize in the broiler diets, without affecting production performance.